Association between social network and dietary variety among community-dwelling older adults - Miyuki Yokoro; Naoto Otaki; Tomomi Imamura; Norikazu Tanino; Keisuke Fukuo (Cambridge University Press, 2023)
Abstract Objective: Social networks are critical social health factors for older adults. This study examined the association between social networks and dietary variety among community-dwelling older adults. Design: A cross-sectional study, using the dietary variety score (DVS) developed for older Japanese people to assess dietary variety and the Lubben Social Network Scale (LSNS-6) to assess social networks. Setting: N City, H Prefecture, Japan. Participants: Community-dwelling older adults aged ≥ 65 years (n 1229). Results: The LSNS-6 score in the low DVS group was lower than that in the middle and high DVS groups (12·2 ± 5·6 v. 13·4 ± 5·4 and 14·4 ± 5·7, P < 0·001). The population of social isolation (LSNS-6, < 12) in the low DVS group was higher than that in the middle and high DVS groups (43·5 % v. 35·8 % and 31·0 %, P = 0·005). Multivariate linear regression analysis showed that the LSNS-6 score was positively correlated with DVS (standardised coefficient, 0·092; P = 0·002). Social isolation was also significantly associated with a low DVS in the multivariate-adjusted logistic analysis model (OR, 1·30; 95 % CI 1·00, 1·68; P = 0·048). Stratified analysis results revealed the LSNS-6 and DVS were significantly associated in participants with the following characteristics: younger age (< 75 years), women and those living with someone. Conclusions: Social networks were associated with dietary variety; social isolation was related to poor dietary variety among community-dwelling older adults. An association between social networks and dietary variety was observed among young-old older adults, women and those living with someone.